A Measure of Export Market Orientation: Scale Development and Cross-Cultural Validation - Cadogan, John W.; Diamantopoulos, Adamantios; de Mortanges, Charles Pahud (Journal of international business studies, 1999)
This study reports on the construction and psychometric assessment of a measure of export market orientation. Four multi-item scales were developed showing strong evidence of reliability and convergent, discriminant, and nomological validity in samples of U.K. and Dutch exporters. Further analysis revealed full invariance of the final measure across the two country samples. Several suggestions for applying the measure in substantive research are offered.